KEPUASAN KERJA KARYAWAN PT ANUGERAH LELANG INDONESIA DIPENGARUHI GAYA KEPEMIMPINAN, KERJASAMA TIM, KOMUNIKASI DAN MOTIVASI - Anggraini, Indar; Ariani, Misna; Arrywibowo, Imam (Jurnal GeoEkonomi, 2025)
This research was used to determine the influence of Leadership Style, Teamwork, Communication and Motivation on Job Satisfaction at PT Anugerah Lelang Indonesia. The population in this research is all employees of PT Anugerah Lelang Indonesia with a total of 35 respondents who will be used as samples. The type of research used is quantitative research with purposive sampling techniques and data collection through distributing questionnaires. This research method uses Smart-PLS data processing with an analysis model using outer model, inner model, basic equations and bootstrapping testing. Based on the results of this research, it shows that the variables of leadership style, teamwork, communication and motivation influence job satisfaction at PT Anugerah Lelang Indonesia